L1 retrotransposition is activated by Ten-eleven-translocation protein 1 and repressed by methyl-CpG binding proteins - Zhang, Peng (Nucleus, 2017)
One of the major functions of DNA methylation is the repression of transposable elements, such as the long-interspersed nuclear element 1 (L1). The underlying mechanism(s), however, are unclear. Here, we addressed how retrotransposon activation and mobilization are regulated by methyl-cytosine modifying ten-eleven-translocation (Tet) proteins and how this is modulated by methyl-CpG binding domain (MBD) proteins. We show that Tet1 activates both, endogenous and engineered L1 retrotransposons. Furthermore, we found that Mecp2 and Mbd2 repress Tet1-mediated activation of L1 by preventing 5hmC formation at the L1 promoter. Finally, we demonstrate that the methyl-CpG binding domain, as well as the adjacent non-sequence specific DNA binding domain of Mecp2 are each sufficient to mediate repression of Tet1-induced L1 mobilization. Our study reveals a mechanism how L1 elements get activated in the absence of Mecp2 and suggests that Tet1 may contribute to Mecp2/Mbd2-deficiency phenotypes, such as the Rett syndrome. We propose that the balance between methylation “reader” and “eraser/writer” controls L1 retrotransposition.